Prison, technology, and consumption: A visual study of the use of electronic commerce strategies in the inmate package industry - Arriagada, Isabel (Theoretical criminology, 2023)
In recent years, the US penal system has increasingly contracted prison services and introduced electronic commerce technologies for penal populations and their social networks. This study uses visual and textual analysis of 245 images from the websites of 17 inmate package companies to explore electronic commerce strategies in US penal institutions. The inmate package industry uses electronic commerce strategies that address the distinctive conditions of penal confinement and deploys emotionally charged messages to encourage digital interactions with the penal system and elicit consumption. Several company websites also organize the experience of consumption along gender and racial lines. The emergent industry of inmate packages represents one among several contemporary practices of carceral consumption.